Bina Damai Keterlibatan Perempuan dalam Aksi Terorisme: Pendekatan Interdisipliner dan Multidisipliner: Peacebuilding Women's Involvement in Terrorism: Interdisciplinary and Multidisciplinary Approaches - Chaerunnisa, Luq Yana; Nasution, Khoiruddin (FAI UIM, 2023)
The case of the bombing in Surabaya carried out by one family and the action carried out by a woman with the initials ZA was shot dead by the Indonesian National Police at the Jakarta Police Headquarters after carrying out the action with a 'soft-gun' pistol against several security officers there, show that women are actively involved. in acts of terrorism. In this case, several approaches are needed to determine the factors of women's involvement as well as peacebuilding actions to overcome them. The approach in question is an interdisciplinary and multidisciplinary approach. Based on this, the purpose of this study is to determine the factors of involvement and the process of developing women's peace in acts of terrorism. The method used to collect data related to the involvement of women in acts of terrorism is literature review. That the involvement of women in acts of terror is not only in the name of religion, but from various aspects of life that can be traced using an interdisciplinary and multidisciplinary approach.